Study on Structure Design and Motion Characteristics of Pneumatic Flexible Wrist with Braking Function - Hongbo Liu; Qi Liu (Applied Bionics and Biomechanics, 2023)
A flexible pneumatic wrist with spatial position maintenance function is developed in this paper to settle the matter of insufficient flexibility of the robot wrist and self-braking technology. The wrist is made up of four artificial muscles and a pneumatic spherical brake in parallel, with 2 degrees of freedom. The wrist can realize multidirectional bending and adjust the wrist damping and braking in real time as required to achieve position maintenance. The theoretical model of the wrist bending angle is built based on torque balance. The variation of wrist bending angle and motion trajectory with air pressure is acquired through experiments. Simultaneously, the validity of the bending angle theoretical model is verified experimentally. A normally open pneumatic spherical brake is developed, and the mathematical model of braking torque is built and experimentally validated. Using a 3D dynamic capture system to compare the dynamic characteristics of the wrist under different excitation signals and different damping conditions. The experimental results reveal that the wrist has good flexibility and can achieve the functions of human hand pitch and yaw. The bending angle is 20.72° at 0.34 MPa. The pneumatic spherical brake has the function of spatial multidirection braking, and the braking force is adjustable. The maximum braking torque can reach 1.4 N m at 0.35 MPa.